Surgical Resection Margins after Breast-Conserving Surgery: Senonetwork Recommendations. Issue 3 (May 2016) - Galimberti, Viviana; Taffurelli, Mario; Leonardi, Maria Cristina; Aristei, Cynthia; Trentin, Chiara; Cassano, Enrico; Pietribiasi, Francesca; Corso, Giovanni; Munzone, Elisabetta; Tondini, Carlo; Frigerio, Alfonso; Cataliotti, Luigi; et al.
This paper reports findings of the "Focus on Controversial Areas" Working Party of the Italian Senonetwork, which was set up to improve the care of breast cancer patients. After reviewing articles in English on the MEDLINE system on breast conserving surgery for invasive carcinoma, the Working Party presents their recommendations for identifying risk factors for positive margins, suggests how to manage them so as to achieve the highest possible percentage of negative margins, and proposes standards for investigating resection margins and therapeutic approaches according to margin status. When margins are positive, approaches include re-excision, mastectomy, or, as second-line treatment, radiotherapy with a high boost dose. When margins are negative, boost administration and its dose depend on the risk of local recurrence, which is linked to biopathological tumor features and surgical margin width. Although margin status does not affect the choice of systemic therapy, it may delay the start of chemotherapy when further surgery is required.